Implikasi Kegiatan Praktek Keahlian Dan Profesi Guru Terhadap Motivasi Belajar Siswa Di MA Al Musaddadiyah Garut Tahun Pelajaran 2022-2023 - Sulaiman, Husnan; Nisa, Nuriyah Rahmi Hoerun (STAI Al-Musaddadiyah Garut, 2023)
Student learning motivation is anything that drives student behavior, whether it arises within the student (intrinsic) or from outside the individual student (extrinsic). Learning motivation is very important in the learning process to achieve student success in learning. However, in fact the learning motivation of students at MA Al Musaddadiyah Garut shows that it is still low, this is evidenced by the findings of researchers on learning continuity, such as; there are students who skip school, are late for class, are lazy to do assignments, lack enthusiasm in learning, are bored in the learning process and are in class but do not pay attention to the teacher. Professional Skills Practice (PKP) is one of the training programs given to students of the Islamic Religious Education (PAI) study program which aims to train students to become professional teachers. Thus the researcher will reveal how the process of prospective PAI Teacher students forms himself, is printed his cognitive, mindset so that he is directed to become a profession as a teacher. The purpose of this study was to find out the implications of teacher professionalism and professional practice activities on student learning motivation at MA Al Musaddadiyah Garut for the 2022-2023 academic year. The method used is an analytical descriptive qualitative method, namely a method that aims to describe, describe, and describe in a comprehensive and complete manner related to research. The data sources used in this study are primary sources and secondary sources. Data collection techniques in this study were observation, interviews and documentation. The data analysis techniques in this study are data reduction, data presentation, and drawing conclusions. Abraham Maslow developed a model of a hierarchy of needs in understanding student learning motivation, namely: Physiological Needs, Safety Needs, Belongingnees and Love Needs, Esteem Needs, and Self-Actualization Needs. The results of this study indicate that the Implications of Teacher Professional Skills Practice Activities on Learning Motivation Students are able to fulfill 4 out of 5 indicators of learning motivation including Safety Needs, Belonging Needs and Love Needs, Esteem Needs, and Self-Actualization Needs. Keywords: Student motivation: Professional Skills Practice (PKP)